KONTRIBUSI KONDISI LINGKUNGAN KELUARGA DAN SEKOLAH TERHADAP HASIL BELAJAR SENI RUPA DI SMA N 9 PADANG - Drs. Yusron Wikarya, M.Pd., VENA MITA SARI, Drs. Eswendi, M.Pd., (Jurusan Seni Rupa FBS UNP Padang, 2017)
This research aims: 1) environmental conditions contribute to the learning outcomes family of fine arts students of SMAN 9 Padang, 2) the contribution of school environment on learning outcomes, 3) the contribution of family and school environment on learning outcomes , Type descriptive correlational. The study population numbered 805 students. The research sample 93 students. Questionnaire tested for validity and realibilitasnya. Hypothesis analysis using linear regression analysis formula is simple and multiple linear regression analysis. RESULTS: (1) there is a significant contribution to the family environment learning outcomes of 22.8%. (2) there is a significant contribution to the school environment learning outcomes 37.9%. (3) the family and school environments contribute to the learning outcomes by 45%.Keywords: Family Environment Condition, School Environment Condition, Learning Result of Fine Arts.